2007
DOI: 10.1370/afm.678
|View full text |Cite
|
Sign up to set email alerts
|

Acanthosis Nigricans and Diabetes Risk Factors: Prevalence in Young Persons Seen in Southwestern US Primary Care Practices

Abstract: PURPOSE Evidence shows acanthosis nigricans is often associated with hyperinsulinemia and may indicate increased risk of type 2 diabetes mellitus. The purpose of this study was to determine the association of acanthosis nigricans with type 2 diabetes risk factors and disease in young persons. METHODSWe conducted a cross-sectional study in the Research in Outpatient Settings Network, a practice-based research network in southwestern US communities. Participating clinicians (N = 96) collected data on children an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
90
1
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(113 citation statements)
references
References 23 publications
16
90
1
6
Order By: Relevance
“…Further, Katz and Feldman, [25] also reported that subjects with AN were also at risk for atherosclerotic cardiovascular diseases. Our findings on high BMI, risk for T2D and CVD and the presence of AN are supported by other studies [26][27][28]. Hirschler et al [26] found that the presence of AN is likely to correlate with BMI.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Further, Katz and Feldman, [25] also reported that subjects with AN were also at risk for atherosclerotic cardiovascular diseases. Our findings on high BMI, risk for T2D and CVD and the presence of AN are supported by other studies [26][27][28]. Hirschler et al [26] found that the presence of AN is likely to correlate with BMI.…”
Section: Discussionsupporting
confidence: 91%
“…In general, the presence of AN is likely to correlate with BMI [26] and high BMI has been shown to be associated with risk for T2D and CVD in several studies [27,28]. Acanthosis Nigricans and the associated IR is common among obese minority adolescents such as Native Americans, African Americans and Hispanics [29], similar results are expected among Jamaican adolescents, many of whom are of African descent and who are already showing signs of being overweight.…”
Section: Introductionmentioning
confidence: 84%
“…24,25 In a study involving 34 obese individuals of both sexes in a predominantly black population (59%), Hud et al reported prevalence of AN in 74% of the patients and demonstrated clear predominance of AN in dark-skinned and black women in relation to white women. 19 Stoddart et al (2002) and Kong et al (2007) recognized AN as an independent risk factor associated with hyperinsulinemia, with the development of DM. 26,27 Kong showed that children with a family history of type 2 diabetes presented AN more often and that acanthosis was more frequent in patients with hypertension and high BMI.…”
Section: Acanthosis Nigricansmentioning
confidence: 99%
“…13,14 The study protocol required data collection and AN diagnosis at the time of the patient encounter but included no patient intervention.…”
Section: Original Prevalence Studiesmentioning
confidence: 99%
“…In a study of the prevalence of Acanthosis Nigricans (AN, a skin condition often associated with hyperinsulinemia) and diabetes risk factors, several clinicians reported that making a diagnosis of AN resulted in changes in the dynamics of the encounter. 13 Reportedly, more time was spent on preventive counseling than would have been the case without diagnosing AN.…”
mentioning
confidence: 99%